2021
DOI: 10.1002/cncr.33984
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes in patients with advanced and/or metastatic non–small cell lung cancer who completed 2 years of immune checkpoint inhibitors or achieved a durable response after discontinuation without disease progression: Multicenter, real‐world data (KCSG LU20‐11)

Abstract: BACKGROUND: Immune checkpoint inhibitors (ICIs) have shown significant improvements in patients with advanced non-small cell lung cancer (NSCLC). One of the major issues with ICIs is determining the optimal treatment duration. METHODS: This multicenter, retrospective study analyzed clinical outcomes in patients with NSCLC who completed 2 years of ICI therapy or were treated for more than 6 months and then discontinued ICIs without disease progression at 11 medical centers in Korea between August 2017 and Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 23 publications
0
26
1
Order By: Relevance
“…Furthermore, we would propose discontinuation of immunotherapy before the standard 2 years of treatment, if ctDNA measurements reach the limit of detection, based on the certain ctDNA response we observed in all long-term responders. Thereby, it would be possible to explore the optimal duration of immunotherapy, as empasized in recent studies ( 55–57 ). A noninferiority study design is required with primary endpoint being OS—and secondary endpoints being PFS by radiologic evaluation and by ctDNA measurements, number of treatment cycles, adverse events, and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we would propose discontinuation of immunotherapy before the standard 2 years of treatment, if ctDNA measurements reach the limit of detection, based on the certain ctDNA response we observed in all long-term responders. Thereby, it would be possible to explore the optimal duration of immunotherapy, as empasized in recent studies ( 55–57 ). A noninferiority study design is required with primary endpoint being OS—and secondary endpoints being PFS by radiologic evaluation and by ctDNA measurements, number of treatment cycles, adverse events, and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Further stratified analysis showed that CR/PR patients is benefit from continuous treatment, while for SD patients, the median PFS of continuous treatment and 1-year fixed treatment was similar, suggesting that continued treatment was more meaningful for CR/PR patients ( 118 ). A multicenter retrospective study from Korea reported the long-term follow-up results in patients with advanced and/or metastatic NSCLC ( 119 ). For patients who completed 2-years ICIs therapy, the 1-year PFS and OS were 81.1% and 96.4%, respectively.…”
Section: Optimal Durations Of Icismentioning
confidence: 99%
“…And for patients who discontinued ICIs after more than 6 months of treatment without disease progression, the 1-year PFS and OS were 71.0% and 90.0%, respectively. Among them, the risk of relapse was significantly higher for treatment duration of 6-12 months but did not differ between 12-18 or 18-24 months ( 119 ). Bilger reported that NSCLC patients who chose to discontinue the drug after at least 18 months of ICIs therapy had 1-year PFS and OS of 71% and 90%, and 2-year PFS and OS of 63% and 84%, respectively ( 120 ).…”
Section: Optimal Durations Of Icismentioning
confidence: 99%
“…It was found that a significantly high proportion of patients who completed 2 years of ICIs therapy continued to experience long-term PFS. Even if ICIs were discontinued in patients without disease progression after 6 months administration, they might achieve a durable response and facilitate long-term survival ( 48 ). In an observational cohort study, 52 patients with metastatic melanoma who discontinued anti-PD-1 therapy after one year remained free of disease progression in the long-term follow-up, and the risk of disease progression was low even in patients with remnant lesions by imaging ( 49 ).…”
Section: Debate For Limited or Continuous Icismentioning
confidence: 99%